Achieving the Legal Objective of Withholding Income Tax on Foreign Youtube Video Creators for Video Utilization Income Sourced in Indonesia - Pangaribuan, Freddy Leonardo; Ritonga, Anshari; Budi, Henry Soelistyo (Universitas Pelita Harapan, 2024)
One of the digital economy transactions is the transaction on YouTube monetization received by video creators based on viewers in a source country. Overseas video creators do not pay Income Tax (PPh) in Indonesia on income from Youtube videos sourced in Indonesia because there is no physical presence of the video creator in Indonesia and no identified income as a tax object on which the Indonesian tax authorities impose PPh on the overseas video creator. This condition creates legal uncertainty, injustice, and loss of benefit for Indonesia as a source country due to the loss of potential PPh revenue from the digital market. Currently, Article 32A of the General Provisions and Tax Procedures (KUP) Law has provided a formal tax law to be able to appoint other parties as PPh withholders. However, the implementation is not yet possible because the material tax law is not yet sufficient to designate other parties, such as Google, which are not domiciled and have no permanent establishment in Indonesia as PPh withholders. To achieve legal objectives, the PPh Law as material tax law needs to be strengthened to provide legal certainty in the PPh withholding on foreign video creators and create justice and benefits for Indonesia as one of the source countries for video creators' income. Strengthening the PPh Law is conducted by amending the provisions of Article 26, Article 2 paragraph (4), and Article 4. The amendment to the PPh Law does not result in revisions of the P3B Indonesia and other countries since the allocation of taxation rights for royalty income from the source country has been regulated in the P3B. Furthermore, the government could make implementing regulations regarding the PPh withholding by other parties on income from the utilization of content copyrights received by YouTube video creators.